The Effect of Mean Years of Schooling, Open Unemployment Rate and Poverty on the Human Development Index in Java Island 2015-2024 - PUTRI, Reva Amanda; DEWI, Dita Dismalasari (PT Keberlanjutan Strategis Indonesia, 2025)
This study aims to analyze the effect of Mean Years of Schooling, Open Unemployment Rate, and Poverty on the Human Development Index in Java Island from 2015 to 2024. The data used is secondary data, with the analysis method used being panel data regression, and the model selected is the Fixed Effect Model. The econometric testing includes classical assumption testing, as well as t-tests, F-tests, and the coefficient of determination (R²) to test the hypothesis. The results show that Mean Years of Schooling has a significant positive effect on the Human Development Index, while Open Unemployment Rate and Poverty have a significant negative effect. This study proves that these three variables simultaneously have a significant impact on human development in Java, where improvements in education quality drive the human development index, while high unemployment and poverty are major obstacles to the human development index that must be addressed immediately.